Clustered Transcription Initiators and Expression of HMW‐GS Genes in Wheat Endosperm. Issue 1 (22nd December 2016) - Jiang, Peihong; Gao, Jiansheng; Zheng, Xiaoran; Feng, Jianing; Xue, Jiesheng; Duan, Luning; Gu, Yunsong; Li, Yaxuan; Yan, Yueming; Li, Xiaohui
Abstract : High‐molecular‐weight glutenin subunit (HMW‐GS) possessing nutritional and bread‐making quality is highly expressed in endosperm of wheat ( Triticum aestivum L.) and its relative species. The main aim of this study was to explore the transcription initiator characteristics correlating to the high‐level expression of HMW‐GS genes. The 5′‐untranslated regions of HMW‐GS gene Ax null, Dx2, Bx7, By8, and Dy12 in cultivar 'Chinese Spring' were cloned by 5′‐full rapid amplification of complementary DNA ends technology. The HMW‐GS gene contained generally three or four transcription initiators, which tightly clustered in a region of 15 nucleotides. The consensus sequence of initiators I, II, and III was an adenine flanked by two pyrimidine bases on each side, namely, YYAYY. The transcriptional initiation efficiencies of these initiators varied dramatically from 3.3 to 90%, and initiators I and II adjacent to the 5′‐end together contributed 83.3 to 93.4%. A mutation from A to T at transcription start site in Ax null worked at far lower efficiency than its counterpart I in Dx2, Bx7, By8, and Dy12 . Our results indicated that the initiator cluster contributed to the high‐level expression of HMW‐GS genes in wheat endosperm. Understanding the mechanism involved in the high‐level expression may be applied in plant breeding for improving agronomic traits of crops, e.g., qualities, yields, growth, or resistance to stress.